Occurrence of antibiotic resistant pathogenic Escherichia coli in cattle, farm environment, milk and beef - Shah, Mian Khaqan (2017)
Antibiotic usage is one of the key factor which has been widely reported to cause the emergence and spread of antibiotic resistant microorganisms in both humans and animals. Animals may be affected with antibiotic resistant pathogenic E. coli being resistant to one or more antibiotics. The increase in multidrug drug resistance (MDR) among bacterial pathogens is a global threat for both human and animal health. Due to the limited data on the occurrence of multidrug resistant pathogenic E. coli in cattle, farm environment, milk and beef in Malaysia, the current study was carried out. The specific objectives were to determine the occurrence of pathogenic E. coli in cattle, farm environment, milk and beef retailed in the markets and to determine the antibiotic resistance and MDR profiles of the isolates. A total of 222 samples were collected from eight farms and 60 beef samples from seven markets. In each farm, 12 faecal samples and 12 environmental samples were collected which included three samples each of feed, water from drinking buckets, swabs of the floor of stall and pooled samples of house flies which consisted, 5-7 flies per pooled sample. Thirty milk samples were collected from five dairy farms which consisted six milk samples in each farm. Beef samples were randomly chosen from retail stalls in each market. The number of beef samples collected in each visit to the markets varied from 6 to 18 per market, depending on the number of beef retailers in that market. Escherichia coli were isolated using conventional isolation methods. Immunomagnetic separation (IMS) technique was used to obtain higher concentration of E. coli O157 and then cultured on Sorbitol MacConkey agar supplemented with Cefexime Tellurite and on Chromagar O157. The suspected colonies were subjected to biochemical tests to identify E. coli. A total of 55.2% (53/96) faecal samples and 43.7% (42/96) farm environmental samples were positive for E. coli. Among the environmental samples, E. coli were isolated from 37.5% (9/24) of feed, 62.5% (15/24) of floor of stalls, 33.3% (8/24) of pooled flies and 41.6% (10/24) of water. Escherichia coli were isolated from 33.3% (10/30) milk samples and 10% (6/60) of beef samples. The E. coli isolates were then screened for E. coli O157 using Dry Spot Latex agglutination test (Oxoid). A total of 33.3% (20/60) isolates from dairy cattle farms, 40% (18/45) isolates from beef cattle farms and 33.3% (2/6) beef in the markets were presumptively identified as E. coli O157. The confirmation of the E. coli O157 and pathogenic E. coli isolates was done by multiplex PCR (m-PCR) using five sets of primers, which were optimized to detect the presence of pathogenic E. coli genes namely st, lt, Ial, rfbO157 and fliCH7 in one single reaction tube. However, all isolates were found negative for st andlt (ETEC),Ial(EIEC), rfbO157 (E. coli O157) genes indicating the absence of pathogenic E. coliwhile four (3.6%) isolates from cattle were positive for fliCH7 (H7). The findings of this study showed high antibiotic resistance and MDR in E. coli isolated from beef cattle, dairy cattle, farm environment, milk and market beef. Escherichia coli isolates from cattle and farm environment showed resistance to all 12 antibiotics tested. The antibiotic resistance of E. coli isolates from cattle faeces and farm environment was observed to penicillin at 93.7%, erythromycin 61%, gentamicin 2.1% and streptomycin 8.4%, while no resistance was observed to ciprofloxacin, norfloxacin and enroflocxacin. Among E. coli isolates from milk, the resistance observed to erythromycin and penicillin was 100%, to ampicillin and tetracycline at 50%, streptomycin, amoxicilline-clavalunic acid and trimethoprim-sulfamethoxazole at 20% while no resistance was observed against ciprofloxacin, gentamicin, cefotaximine, norfloxacine and enroflocxacine. Escherichia coli isolates from beef showed resistance to all antibiotics. The resistance against ampicillin, erythromycin, penicillin and amoxicilline-clavalunic acid was 100% while to ciprofloxacin, gentamicin and norfloxacin was 16.7 %. The multidrug resistance among E. coli isolates from cattle faeces, farm environment and milk was 44.2 %, 52.5% and 70% respectively. The highest MDR observed was 100% in E. coliisolates from beef. The absence of pathogenic E. coli may possibly indicate that dairy and beef cattle in these farms are not reservoirs of ETEC, EIEC, EHEC (E. coli O157). However, the risk of other zoonotic strains of pathogenic E. coli for humans is a rising concern because they may be present in the food chain. The presence of high MDR E. coli species could pose a serious threat towards compromising the treatment in humans, as bacteria are resistant to the drugs of choice and therefore is of an important concern and significant public health risk. Certainly, the prevalence of MDR E. coli in cattle farms, milk and market meat should be monitored. The awareness of farmers and meat sector workers towards hygienic measures should be practiced and there should be prudent use of antibiotics to control antibiotic resistance.